TERAPI LATIHAN PADA PASIEN LUKA GANGRENE UNTUK MEMINIMALKAN RISIKO AMPUTASI DI RS EFARINA BERASTAGI - Muliati, Muliati; Marolop Parlindungan Napitu; Isa Harpika Br. Ginting; I Ngurah Gede Verar Fujastawan; Margaretha Togatorop (Nusantara Hasana Journal, 2025)
Gangrene wounds are a serious condition characterized by tissue death due to impaired blood circulation and infection, which carry a high risk of amputation if not properly managed. Exercise therapy is a non-pharmacological intervention that can help improve blood circulation, maintain limb function, and accelerate wound healing. This study aims to determine the effectiveness of exercise therapy in minimizing the risk of amputation in patients with gangrene wounds at Efarina Berastagi Hospital. The method used was a descriptive approach with a structured exercise program including range of motion exercises, muscle strengthening, and circulation exercises. The results showed that patients who regularly performed exercise therapy experienced improvement in tissue condition, reduction in edema, and increased functional ability. In addition, the risk of amputation could be reduced through improved tissue perfusion and better infection control. Therefore, exercise therapy can be an important component in the comprehensive management of patients with gangrene wounds